Determination Of Haematological And Endogenous Steroids Profiles In Malaysian Junior Athletes - Mohd Rodhi, Ainolsyakira (2019)
Haematological and steroidological profiles have been used by World Anti-Doping Agency (WADA) to monitor the use of banned substances among athletes. These profiles can be highly influenced by many factors such as gender, physical activity, dietary, geographical factors and genetic origins. Establishing reference values of steroids and haematology profile in laboratory could be beneficial as it can compensate for the difference in local athletes. The aims of this study were to establish haematological and steroidological reference values for local athletes and to compare the variation of these values on several subpopulations. Blood and urine samples were collected from 126 athlete and 39 non-athlete subjects from three major ethnic groups within five consecutive weeks.